Thymoquinone Reverses Homocysteine-Induced Endothelial Dysfunction via Inhibition of Endoplasmic Reticulum-Stress Induced Oxidative Stress Pathway - SITI SARAH, M. SOFIULLAH; DHARMANI DEVI, MURUGAN; SUHAILA, ABD MUID; Wu, Yuan Seng; Nor Hisam, Zamakshshari; QUAN, FU GAN; MELONNEY, PATRICK; NORASIKIN, AB AZIS; SRINIVASA RAO, SIRASANAGANDLA; Choy, Ker Woon (Penerbit UKM, 2024)
Hyperhomocysteinemia causes endoplasmic reticulum (ER) stress, which elevates reactive oxygen species (ROS) and induces endothelial dysfunction, the hallmark of cardiovascular diseases. Nigella sativa seeds contain thymoquinone (TQ), a cardioprotective bioactive component. Nevertheless, research on investigating the effectiveness of TQ in preventing endothelial dysfunction caused by homocysteine (Hcy) is scarce. Therefore, the purpose of this work was to examine the role of TQ in restoring Hcy-induced endothelial dysfunction as well as the mechanisms behind this role. Male Sprague-Dawley (SD) rat aortas were isolated and then co-treated in an organ bath with Hcy and TQ, tauroursodeoxycholic acid (TUDCA), apocynin, or Tempol to examine vascular function. Furthermore, human umbilical vein endothelial cells (HUVECs) were treated with Hcy and TQ, Tempol, apocynin, TUDCA or H2 O2 to determine the cell viability via a phase contrast microscope and dye exclusion test. ER stress pathway involvement, ROS and NO bioavailability were investigated using immunoassays and fluorescence staining, respectively. The binding affinity of TQ to GRP78 has been identified using molecular docking. According to our findings, Hcy hindered endotheliumdependent relaxation in an isolated aorta and caused apoptosis in HUVECs. TQ, TUDCA, Tempol, and apocynin were able to counteract these negative effects. In HUVECs, treatment with TQ decreased ROS levels, increased NO bioavailability, and decreased GRP78 and NOX4 protein. According to the molecular docking study outcomes, TQ could attach to GRP78 effectively via a hydrogen bond and a hydrophobic connection to the amino acid at GRP78 ATP binding pocket. Taken together, the findings show that TQ protected endothelial function caused by Hcy via inhibiting ER stress-mediated ROS and eNOS uncoupling.